Bioconversion of isoflavones glycoside to aglycone during edamame (Glycine max) soygurt production using Streptococcus thermophillus FNCC40, Lactobacillus delbrueckii FNCC41, and L. plantarum FNCC26 - NOVILA SANTI LOVABYTA; Jay Jayus; ARI SATIA NUGRAHA (Society for Indonesian Biodiversity, 2020)
Abstract. Lovabyta NS, Jayus J, Nugraha AS. 2020. Bioconversion of isoflavones glycoside to aglycone during edamame (Glycine max) soygurt production using Streptococcus thermophillus FNCC40, Lactobacillus delbrueckii FNCC41, and L. plantarum FNCC26. Biodiversitas 21: 1358-1364. Due to its strong radical-scavenging and antioxidative activity, isoflavones in soybeans have received great attention for the development of functional foods. This study focused on bioconversion of isoflavones glycoside into its aglycone form of edamame green soymilk fermented with three lactic acid bacteria (LAB), i.e., S. thermophilus FNCC40, L. bulgaricus FNCC41, and L. plantarum FNCC26 to produce soygurt. Green soymilk was fermented with 6% (v/v) of LABs as a starter culture for 24 hours at 37ºC. Its antioxidative activity were measured using DPPH free radical scavenging activity method. Daidzein and genistein released during fermentation were fractionated using HPLC and detected further by LCMS to confirm the presence of these two substances. The results showed that the population density of starter culture in green soymilk reached 109 CFU/mL, and the pH decrease from 6.8 to 3.5. All LABs cultures used in the fermentation process were able to produce free aglycone, releasing more daidzein and genistein. Increasing daidzein and genistein content in soygurt results in increasing antioxidative activity. The highest antioxidative activity (IC50 = 41.01 mg/mL) was found in the soygurt fermented with S. thermophilus FNCC40. This finding indicates that S. thermophilus FNCC40, L. bulgaricus FNCC41, and L. plantarum FNCC26 are potential as an effective starter culture to produce a soygurt with good antioxidant activity.